PENGARUH PENDEKATAN COMPREHENSIVE MATHEMATICS INSTRUCTION BERBANTUAN POWERPOINT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Nila Sri Wijayanti, - (2022)
The low mathematical problem solving ability of students is the reason behind this research. As an alternative solution to solving mathematical problems, research was conducted by applying the Powerpoint-assisted Comprehensive Mathematics Instruction (CMI) approach. The purpose of this study was to determine the effect of the powerpoint-assisted CMI approach on mathematical problem solving abilities. A quasi-experimental research method was used with a population of all fifth grade elementary school students in Sumedang Regency. The sample selection used cluster sampling technique and obtained two classes that were used as research samples. The research instrument is a test of mathematical problem solving abilities, observations of teacher performance and student activities, and field notes. The results of statistical analysis with = 0.05, it was concluded that learning using the CMI approach assisted by powerpoint had a positive effect on mathematical problem solving abilities. The conventional approach also has a positive effect on mathematical problem solving abilities. Then, there are differences in the effect of the Powerpoint-assisted CMI approach on students' mathematical problem solving abilities. The PowerPoint-assisted CMI approach becomes a recommendation to develop students' mathematical problem solving abilities. Keywords: Powerpoint Assisted CMI Approach, Powerpoint, Mathematical Problem Solving Ability.